Archaean and palaeoproterozoic migmatizations in the Belomorian Province, Fennoscandian Shield: Petrology, geochronology, and geodynamic settings - Slabunov, A. I.; Azimov, P. Ya.; Glebovitskii, V. A.; Zhang, L.; Kevlich, V. I. (Doklady Earth Sciences, 2016)
Multiple repetitions of migmatization processes are an important indication of the polychronous evolution of Precambrian Mobile Belts: this is certainly true for the Belomorian Belt. In the Belomorian Province of the Fennoscandian Shield, newly obtained data demonstrate the effect of two stages of melting of the Earth's crust under conditions of higher pressure up to 8-14 kbar. The early stage of the migmatization and genetically related leucogranite formation took place in the Neoarchaean (2710 +/- 15 and 2706 +/- 14 Ma, U-Pb zircon ages), while the younger one happened in the Palaeoproterozoic (1944 +/- 12 and 1882 +/- 9 Ma, U-Pb zircon ages of leucosomes). The early stage of crust melting is related to collision in the Belomorian Neoarchaean orogen, while the later stage occurred during formation of the Lapland-Kola orogen. Russian Foundation for Basic Research [13-05-91162, 15-05-09288]; Presidium of RAS [I.5P, IV.8.8] SCI(E) EI ARTICLE slabunov@krc.karelia.ru 1 259-263 467